Constitutional Politics and the Territorial Question in Canada and the United Kingdom Federalism and Devolution Compared (Comparative Territorial Politics, 2018)
This book compares the constitutional politics in Canada and the United Kingdom - two complex, multilevel, plurinational states. While the former is federal and the latter a devolved state, the logic of both systems is similar: to combine unity with diversity. Both are facing similar challenges in a world marked by spatial rescaling, international interdependence and economic and social change. The contributors chart these challenges and the responses of the two countries, covering the meanings of federalism and devolution; the role of the courts; fiscal equalization; welfare; party politics; reform by popular referendum and citizen assemblies; and intergovernmental relations. The book will be of interest to students of federalism and multilevel government, state transformation territorial politics on both sides of the Atlantic.